Utilization of IoT to Develop an Automation System for Disabled People - khatib, Maher Jamal AL- (IJRDO -Journal of Computer Science Engineering, 2017)
The paper focuses on finding a solution related to Internet of Things that can be used effectively for the disable people. Disable people face difficult in performing their day to day activities, the research is deriving a technique that will be used to help them. Various methods and techniques were studied and an effective solution was decided that will help them in spending their day to day life. The seeker of research noticed the problems in real life and came up with solution to that. Different research methods were used for deriving it. Different Questionnaire were also distributed in Old Age houses also to find the problem that Old people face, as most of old people are also not able to perform their basic day to day activity and can be classified as disable technically, so that the research remains practical and helpful for mankind.